Harboyan Syndrome - Javaid, Ayesha; Orakzai, Abdullah Ahmad (Journal of Ayub Medical College Abbottabad, 2021)
Harboyan syndrome is a degenerative corneal disorder characterized by congenital hereditary endothelial dystrophy along with progressive, post lingual sensorineural hearing loss. We present the case of a 16-year-old female, who came to us for her follow up after surgical correction for bilateral corneal opacities (bilateral keratplasy) and use of hearing aid for SNHL. Her symptoms resolved significantly. Currently, she’s living a healthy life after being treated for Harboyan syndrome. Physical examination and laboratory investigations ruled out other causes (eg: Congenital cataracts, Peters anomaly, Sclerocornea) and the diagnosis of Harboyan syndrome was established. Keywords: Harboyan Syndrome; SNHL; Sensorineural hearing loss; Keratoplasty; CHED; Congenital hereditary endothelial dystrophy